Occlusion pressure and blood pressure adaptations following low-load blood flow restriction training versus moderate-load training: a pilot randomized clinical trial in patients with knee osteoarthritis - Cerqueira, Mikhail Santos; Pereira, Rafael; Maciel, Daniel Germano; Pinto, Cláudia Thais Pereira; Rolnick, Nicholas; Vieira, Wouber Hérickson de Brito (Frontiers in Physiology, 2026)
ObjectiveThis pilot study investigated potential adaptations in limb occlusion pressure (LOP) and compared LOP between low-load resistance training with blood flow restriction (LL-BFR) and traditional moderate-load training (ML) over 9 weeks in patients with knee osteoarthritis (KOA). Secondarily, we compared systolic blood pressure (SBP) and diastolic blood pressure (DBP) adaptations between these groups.MethodsSeventeen KOA patients were randomly assigned to the LL-BFR or ML groups. The LL-BFR group performed 75 repetitions (10% 1RM; 60% of LOP). The ML group performed 24 repetitions (60% 1RM; 10% [SHAM] of LOP). In both groups, exercises involving LOP were bilateral hack machine squat and knee extension exercises. LOP, SBP, and DBP were measured before and every 3 weeks until the ninth training week.ResultsAfter 9 weeks, there were no statistically significant changes in LOP, SBP, or DBP within or between groups. LOP decreased by −32.9 mmHg (95% CI: −68.9 to 3.2) in LL-BFR and −17.2 mmHg (95% CI: −49.0 to 14.6) in ML, achieving clinical significance [relative error variance (REV) = 14.6 mmHg]. SBP decreased by −7.5 mmHg (95% CI: −15.6 to 0.6) in LL-BFR and −1.1 mmHg (95% CI: −8.2 to 6.0) in ML. DBP decreased by −3.7 mmHg (95% CI: −9.2 to 1.7) in LL-BFR and −1.9 mmHg (95% CI: −6.8 to 2.9) in ML.ConclusionWe observed a non-significant trend toward a reduction in LOP following 9 weeks of LL-BFR in patients with KOA, with a mean point estimate that exceeded a pre-defined threshold for clinical significance, although the wide confidence intervals indicate substantial uncertainty. Furthermore, SBP and DBP showed no significant changes, and no group differences emerged across outcomes. Practically, these findings suggest that LOP remains stable throughout a rehabilitation program, potentially reducing the burden of frequent LOP reassessment in clinical LL-BFR applications.Trial registrationhttps://ensaiosclinicos.gov.br/rg/RBR-6pcrfm/.